The Dual Faces of Religion: Tolerance and Intolerance in a Sociological Approach - Rahmat, Efendi; Waluyajati, Roro Sri Rejeki; Huriani, Yeni; Hambali , Radea Yuli Ahmad (Integritas Terbuka: Peace and Interfaith Studies, 2025)
This study aims to explore the dual role of religion in contemporary society—as both a source of tolerance and a driver of intolerance—by critically analyzing the socio-political, cultural, and global contexts that shape religious discourse. The research responds to the urgency of understanding religion beyond theological essentialism, emphasizing the need for a sociological approach to interpret the contradictory manifestations of religion in plural societies. Employing a qualitative design through critical literature review, the study analyzes academic texts and discourse on religion using thematic content analysis. The data sources include influential works by Diana Eck, John Hick, Mark Juergensmeyer, Karen Armstrong, Jeremy Menchik, Robert Hefner, and others. The findings reveal three significant patterns: religion as a moral force fostering interfaith dialogue; religion as an ideological tool legitimizing social exclusion; and the ambivalent image of religion shaped by state politics, popular media, and transnational religious networks. The study demonstrates that religion is never neutral—it is continuously constructed and contested within power relations, identity politics, and symbolic representation. These insights underscore the functional and dysfunctional roles of religion in shaping social cohesion and polarization. The implications of this research highlight the urgency of promoting critical religious literacy, interfaith education, and inclusive public policies that prevent the instrumentalization of religion for sectarian or authoritarian interests. The originality of this study lies in its multidimensional mapping of the social construction of religion, shifting the analytical lens from sacred texts to contextual forces. By integrating classic sociological theories with the Indonesian context, this research offers a comprehensive and contextually grounded contribution to the sociology of religion.